Asset recovery V. human rights: the European Court of Human Rights an the case of Paulet V. Unitred Kingdom - Prieto-del-Pino, Ana María (My University, 2017)
Recovery of assets comming from crime is considered to be one of the most important measures for fighting against organised crime nowadays. However, figures do not seem to give much cause for optimism. According to the most recent data regarding the period 2010-2014 provided by the Europol in 2016, 2.2% of the estimated proceeds of crime were provisionally seized or frozen, however only 1.1% of the criminal profits were finally confiscated at EU level. At the same time, although crime does not pay, those who are innocent should not pay for the guilty ones’ faults and human rights must be preserved. The case law at ECHR acknowledges that confiscation involves control on the use of property but gives the member states a wide margin of assessment as far as determining whether or not the fair balance between the demands of the general interest and the interests of the individual gets broken. In addition to private property, other rights that may be affected by non conviction based confiscation orders are: -criminal sanction by another name (criminal sanction in disguise) -presumption of innocence -reversal of the onus of proof -silence -non retroactivity of penal legislation -access to legal aid.
Keywords: Administración de justicia penal; Asset revovery; Human rights; Criminal law